Nanocomposite complex ZnO in combination with a triazoloazepinium derivative for inhibition of microbial steel corrosion - Demchenko, N.R.; Bondar, O.S.; Tkachenko, S.V.; Кurmakova І.М.; Kupchuk О.Yu.; Derevianko, S.V. (Physics and Chemistry of Solid State, 2024)
We have established the possibility of using ZnO nanoparticles to inhibit microbial corrosion with simultaneous inhibition of growth and sulfate-reducing activity of bacteria of the corrosive active group. The search for ways to increase the antibacterial and anticorrosive effect of ZnO nanoparticles makes it possible to combine them with substances, in particular, inhibitors-biocides of microbial steel corrosion. The nanocomposite complex of ZnO nanoparticles and cationic heterocyclic compound (triazoloazepinium derivative) was studied as a biocide and inhibitor of microbial corrosion on steel. The component concentrations are 3 mg/mL and 1 mg/mL accordingly. The experiments were carried out by using a microbiological and corrosion control methods. It has been established that the proposed nanocomposite complex affects the number of bacteria in the plankton and biofilm. In its presence, there is a complete inhibition of the growth of sulfate-reducing bacteria (the most aggressive component of the microbial community) in plankton. Also, the number of denitrifying bacteria and iron-reducing bacteria in plankton decreases by 3 and 4 orders, respectively. The biofilm formed in the presence of the nanocomposite in the culture medium is less dense in terms of the number of bacterial cells of the sulfidogenic community.